2021
DOI: 10.1017/s1355617721001090
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Phenotypes in Pediatric Temporal Lobe Epilepsy

Abstract: Objective: Adults with temporal lobe epilepsy (TLE) have been found to have a fairly characteristic pattern of neuropsychological performance, but there is considerably less research and more variability in findings with children. Because the cognitive domains included in most studies with children have been limited, the current study attempted to better characterize the cognitive phenotype of children with TLE using a broader neuropsychological battery. Methods: The study included 59 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…For these reasons, recent efforts have turned to identifying unique patterns of cognitive impairment, or cognitive phenotypes, and their associated disrupted networks within and across epilepsy syndromes. Studies in patients with focal epilepsy have typically identified three-to-four unique phenotypes that help to explain the heterogeneity observed at the group level (Baxendale & Thompson, 2020;Elverman et al, 2019;Hermann, et al, 2007;Hermann et al, 2020;Reyes et al, 2019Reyes et al, , 2020Rodríguez-Cruces et al, 2018;Schraegle et al, 2021). Furthermore, these unique phenotypes are characterized by distinct patterns of cortical thinning and subcortical atrophy (Dabbs et al, 2009), network disruption (Hermann et al, 2020;Kaestner et al, 2019;Reyes et al, 2019), risk for cognitive progression (Hermann et al, 2007), and risk for postsurgical decline (Baxendale & Thompson, 2020) that are not always apparent when patients are studied in aggregate.…”
mentioning
confidence: 99%
“…For these reasons, recent efforts have turned to identifying unique patterns of cognitive impairment, or cognitive phenotypes, and their associated disrupted networks within and across epilepsy syndromes. Studies in patients with focal epilepsy have typically identified three-to-four unique phenotypes that help to explain the heterogeneity observed at the group level (Baxendale & Thompson, 2020;Elverman et al, 2019;Hermann, et al, 2007;Hermann et al, 2020;Reyes et al, 2019Reyes et al, , 2020Rodríguez-Cruces et al, 2018;Schraegle et al, 2021). Furthermore, these unique phenotypes are characterized by distinct patterns of cortical thinning and subcortical atrophy (Dabbs et al, 2009), network disruption (Hermann et al, 2020;Kaestner et al, 2019;Reyes et al, 2019), risk for cognitive progression (Hermann et al, 2007), and risk for postsurgical decline (Baxendale & Thompson, 2020) that are not always apparent when patients are studied in aggregate.…”
mentioning
confidence: 99%
“…The present study utilized a similar statistical approach to previously published work examining behavioral phenotypes in children and adults with epilepsy. [26][27][28] Ward's hierarchical agglomerative clustering method was used with the nine BASC-2 clinical scales (Aim 1). 36 Squared Euclidean distance was used as the index of pairwise similarity -dissimilarity between participant profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The test battery was comprehensive and included measures of intelligence, language, visuospatial, immediate verbal memory, delayed verbal memory, executive functioning, and motor dexterity. Cluster analysis identified seven cognitive factors (see Schraegle et al 27 for details) and served as the dependent variables.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations